2013
DOI: 10.1007/s00213-013-3039-3
|View full text |Cite
|
Sign up to set email alerts
|

A double blind, placebo-controlled study of the effects of post-retrieval propranolol on reconsolidation of memory for craving and cue reactivity in cocaine dependent humans

Abstract: Rationale/Objectives This study examined the effects of propranolol vs. placebo, administered immediately after a 'retrieval' session of cocaine cue exposure (CCE), on craving and physiological responses occurring 24 hr. later during a subsequent 'test' session of CCE. It was hypothesized that compared to placebo-treated cocaine-dependent (CD) individuals, propranolol-treated CD individuals would evidence attenuated craving and physiological reactivity during the test session. Secondarily, it was expected that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 88 publications
2
109
1
1
Order By: Relevance
“…In animal studies, propranolol has been shown to inhibit reconsolidation of cocaine-and morphine-conditioned place preference (27,42). Postreactivation propranolol administration also attenuates reconsolidation of memories for craving and cue reactivity in cocaine addicts and abstinent heroin addicts (31,43). Previous studies have shown that Arrb2 −/− mice respond well to cocaine in CPP (44), but not to amphetamineinduced locomotor activity, compared with wild-type mice (45).…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, propranolol has been shown to inhibit reconsolidation of cocaine-and morphine-conditioned place preference (27,42). Postreactivation propranolol administration also attenuates reconsolidation of memories for craving and cue reactivity in cocaine addicts and abstinent heroin addicts (31,43). Previous studies have shown that Arrb2 −/− mice respond well to cocaine in CPP (44), but not to amphetamineinduced locomotor activity, compared with wild-type mice (45).…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol as a Potential Therapeutic: Actions at NE and 5-HT Receptors Propranolol reduces cue-induced reinstatement of cocaine seeking and conditioned place preference (CPP) for cocaine in rodents, as well as cue-induced craving in cocaine-dependent humans (Bernardi et al, 2006;Smith and Aston-Jones, 2011;Saladin et al, 2013). Alternatively, systemic propranolol increased dopamine release in NAc, and reduced cocaine selfadministration indicating that propranolol may increase cocaine's reinforcing efficacy (Harris et al, 1996;Perry et al, 2015).…”
Section: Intakementioning
confidence: 99%
“…Among cocainedependent patients, exposure to drug-associated cues or stressors results in increased adrenocorticotrophic hormone (ACTH), cortisol, and hypothalamic-pituitary-adrenal (HPA) axis activity (Sinha et al, 2000(Sinha et al, , 2003. Among abstinent heroin addicts and cocaine-dependent individuals, propranolol is effective in reducing cortisol-, stress-, or cueinduced cravings Zhao et al, 2010;Saladin et al, 2013). Racemic propranolol antagonizes β-ARs and 5-HT receptors, and therefore these effects may be due to the actions of either of these receptors.…”
Section: Ne and 5-ht Signaling May Converge On Stress Pathways To Infmentioning
confidence: 99%
“…Thus, modification of reconsolidation-related plasticity allows for memory modification and even memory elimination. Reconsolidation is now being studied extensively as disruption of pathologic, emotional forms of memory could alleviate memory-related disorders, such as posttraumatic stress disorder (PTSD; Brunet et al, 2008) and drug addiction (Saladin et al, 2013;Xue et al, 2012).…”
Section: Introductionmentioning
confidence: 99%